MODAL SOSIAL DI DALAM MEMPERTAHANKAN KOMUNITAS (Studi Tentang Komunitas Motor Vespa Uvorable Di Pekanbaru) - Muhammad Ichsan; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describe about the maintain social capital in community vespa uvorable Pekanbaru. Maintaining social capital in the community can be seen through some of the indicators of which is the notion of social capital, social capital in a community, the elements of social capital, the norm in social capital and social networks.The study population was a member of the community joined in uvorable vespa motorcycle community in Pekanbaru. Sampling method used in this study is proportionate stratified sampling techniques and data analysis used is descriptive and qualitative analysis.Data was collected by using questionnaires, interviews and documentation. The theory used is the Social Group Theory and Theory of Social Capital. This study aims to determine the history of the formation of uvorable vespa community, to know what their purpose in forming a community of Vespa unvorable well as to determine the existence of a community of Vespa uvorable Results from this study is that the members of the community joined in Pekanbaru uvorable vespa community have one thought and one purpose the same that they vespa motor fans and they do not want the motor vespa they use now become old items no longer used because of the rapid developments in automotive technology. They want to be recognized by the community with the community joined in a Vespa, the Vespa community uvorable Pekanbaru.Keyword : Social Capital, Social Network, Vespa Community Uvorable in Pekanbaru